(untitled) (Research, Society and Development, 2019)
As the process of financial market integration has intensified, capital mobility has become necessary for markets that have made it possible for investors to see increasing returns associated with lower risks. This study proposes to investigate the increase of foreign investments in the stock exchange after the adoption of the IFRS, in order to know if this adoption had an impact on foreign investments, as well as to identify if there was an increase of new foreign investors after the adoption, to analyze factors that led Brazil to adopt it, to verify if there was variation of the foreign investments in the period of crisis and to characterize foreign and national investments in the diverse markets of the Brazilian stock exchange. The methodology is empirical-analytical, aiming to gather information on the history of foreign and domestic investments and to compare the flow of capital before and after the standardization of IFRS standards. The sample is composed of variables on the volume of foreign and domestic investments on the Brazilian stock exchange in the periods 2004-2009 (before the adoption of IFRS) and 2010-2017 (after the adoption of IFRS). In order to estimate the increase in foreign investments, the Student t-test is used, which uses statistical concepts to reject or not a null hypothesis and is applied whenever one intends to compare the means of a variable. The results show that foreign investments, which were 33% before IFRS, were 44%. It was concluded that the adoption of the IFRS standards provoked an increase in foreign investments, contributing to the country’s economy.